LIMITATION OF LEGAL INSTITUTIONS ASSOCIATED WITH INTERFERENCE IN THE RIGHT OF OWNERSHIP OF THE SUBJECT OF THE ECONOMY - S.S. Yatsenko (Економіка та право, 2018)
The article is devoted to delimitation of nationalization and concepts related to it, namely expropriation, requisition, confiscation, alienation of real estate objects for the reason of social necessity. For this purpose, author identifies competent entity, object of alienation and type of decision in each of specified actions. In article was proven that nationalization is a policy tool and it should be provided by act of legislative body that runs the economic policy. Expropriation can be defined as international concept rather than economic. The related notions were examined as well. Finally, ways for improving the legal regulation were also proposed. The paper is prepared with the complex tools of tax law, criminal law, customs law, sea trade code, civil procedural code etc. The civil procedural code is compared with commercial procedural code in the context of assets arrest. In the paper the certain grounds of such governmental activity stated. One of the examples is the situation with a nowadays state-owned bank "Privatbank". The other is real estate complex of "Mezhihirya". After the paper preparation the conclusions were made, e.g. suggested not to sellout the confiscated equipment, but to transfer this to the state-owned companies; there must be a legal reason for nationalization, in other case the state would not provide such kind of economic policy; each case of state intrusion into the property rights of the business, there should be specific guarantees for the economic system. Suggested to eliminate the using of the word "expropriation" in the national legal field. The objects, subjects and reasons for each of the so-called "acts" are classified in purpose to make a notion of each case .of the deprivation of the private property of the business. Stated, that the principles of economic law must be observed during such activity of the state.